Addressing Comorbidities When Treating Anxious Youth. Issue 1 (2nd January 2018) - Palitz, Sophie A.; Carper, Matthew M.; Kagan, Elana R.; Aggarwal, Richa; Frank, Hannah E.; Davis, Jordan P.; Kendall, Philip C.
ABSTRACT: Anxiety disorders are highly prevalent among youth, with comorbid diagnoses being the norm, not the exception. Few guidelines exist regarding the best approach to treating anxious youth with comorbid mental health conditions. The present article presents a framework to guide clinicians treating anxious youth who present with comorbid (a) depressive disorders, (b) attention deficit/hyperactivity disorder, (c) oppositional defiant disorder, (d) autism spectrum disorder, or (e) other anxiety disorders. We propose three paths for clinicians to consider when treating youth with anxiety and a comorbid disorder: (a) treating the comorbid condition first, (b) treating only the anxiety and referring the youth out for comorbidity-specific treatment, or (c) treating both disorders simultaneously by integrating components of other evidence-based treatments. We conclude with practical implications and a call for future research on the treatment of comorbid diagnoses in youth.